2022
DOI: 10.1097/won.0000000000000851
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Nursing Students' Knowledge of and Attitudes Toward Urinary Incontinence

Abstract: PURPOSE: This study aimed to determine nursing students' knowledge about and attitudes toward patients with urinary incontinence. SUBJECTS AND SETTING: The sample comprised 392 nursing students from 5 educational institutions in Hong Kong; all participants were enrolled in year 4 or 5 of their undergraduate nursing program, and all had completed formal education on urinary incontinence and clinical experience caring for patients with urinary incontinence. METHODS: A cross-sectional survey was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(53 reference statements)
1
0
0
Order By: Relevance
“…Appropriate team collaboration between registered nurses and NAs in daily practice is necessary [ 20 ]. Similar to another study [ 34 ], we found no statistically significant difference in UI attitude scores by sex. NAs with a high school education and those with more UI training experience had more positive attitudes than those with primary school education and those who had less training experience.…”
Section: Discussionsupporting
confidence: 90%
“…Appropriate team collaboration between registered nurses and NAs in daily practice is necessary [ 20 ]. Similar to another study [ 34 ], we found no statistically significant difference in UI attitude scores by sex. NAs with a high school education and those with more UI training experience had more positive attitudes than those with primary school education and those who had less training experience.…”
Section: Discussionsupporting
confidence: 90%